Gestational Diabetes Independently Increases Birth Length and Augments the Effects of Maternal BMI on Birth Weight: A Retrospective Cohort Study - Byström, Magdalena; Liu, Anthony; Quinton, Ann Elizabeth; Champion, Bernard Linton; Mann, Kristy; Peek, Michael; Nanan, Ralph Kay Heinrich (Frontiers in Pediatrics, 2014)
Objective To investigate the effect of the interaction between gestational diabetes (GDM) and maternal body mass index (BMI) on the individual neonatal growth parameters. Design Retrospective cohort study Setting A tertiary maternity service in Sydney, Australia, between 2005 and 2009. Population A cohort of 8859 women. Methods Generalized linear models. Main Outcome Measures Neonatal growth parameters, represented by z-scores for infant birth weight, birth length and head circumference in GDM and non-GDM groups. Results Only GDM alone had an independent and positive effect on birth length (p=0.02) but not on birth weight or head circumference. In addition, in pregnancies complicated with GDM, the association between maternal weight and birth weight was significantly stronger (p<0.001). In combination, GDM and maternal BMI significantly affected z-score differences between birth weight and birth length (p<0.001), in that underweight mothers had babies which were lighter relative to their length and inversely obese mothers had babies which were heavier relative to their length. Conclusions GDM independently influences birth length and increases the association between maternal BMI and birth weight. In accordance with the hypothesis of the fetal origins of health and disease, the pronounced effects of GDM on fetal growth patterns demonstrated in this study are likely to influence long-term health outcomes in children.